Self-Monitoring Interventions for Students With EBD: Applying UDL to a Research-Based Practice. (April 2017) - Cook, Sara Cothren; Rao, Kavita; Collins, Lauren
Students with emotional and behavioral disorders (EBD) have unique academic and behavioral needs that require the use of evidence-based practices. One way that teachers can support students with EBD is by individualizing interventions, such as self-monitoring, while maintaining a high level of fidelity. In this article, the authors describe how the Universal Design for Learning framework can be used to design individualized self-monitoring interventions for students with EBD while still maintaining core components of the intervention.